CONTRIBUTION OF MICRO BUSINESS WOMEN TO THEIR FAMILIES IN SOUTHEAST SULAWESI COASTAL AREA - Hartina Batoa; Munirwan Zani; Putu Arimbawa; Muhammad Aswar Limi; Dasmin Sidu; La Ode Kasno Arif (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2015)
ABSTRACTThe purpose of this study is to analyze the contribution of micro businesses women (MBW) to their business and families. This research was conducted in five districts / cities were determined purposively with consideration of its regional characteristics and business community that generally involved in fisheries subsector. Those five districts are West Muna, South Konawe, Kolaka, Baubau city, and Kendari city. MBW contribution to their business then analyzed using descriptive analysis. MBW contribution to their business also studied by using the amount of working time devoted by MBW in managing and running their business every day approach. Besides that, their contribution also seen by the amount of the capital invested to the business from the revenue. MBW contribution to the families analyzed using MBW revenue contribution to total household income.MBW has a major contribution to the business of the MBW family itself. It can be seen from the amount their working time, that most of MBW routinely do business every day, and only small fraction of MBW that don’t do it daily,with working hours reached 6.35 hours per day and to take care of the household ie 4, 13 hours per day, business activity of MBW is highly dependent on the availability of raw materials such as fresh fish and processed fish, including the availability of capital venture. Related to venture capital factors, there are still few of MBW that have financial capital less than 1 million, but in a big scale there are MBW who have financial capital more than 20 million.Keywords: Women Contribution; Micro business; coastal Area.